Innovative Line for Door Production TechnoPORTA—Technological and Economic Aspects of Application of Wood-Based Materials - Zdzisław Kwidziński; Joanna Bednarz; Marta Pędzik; Łukasz Sankiewicz; Piotr Szarowski; Bartłomiej Knitowski; Tomasz Rogoziński (Applied Sciences, 2021)
Material losses are caused by the machining process and the manufacturing process, as well as the use of excessive dimensional allowances applied to the machined materials. An adequate reduction of the planned machining allowances for wood-based panel components is possible when the machining line is properly designed and equipped with high-precision machines and devices. The aim of the study was to determine the size of material savings in relation to the most important construction materials when implementing an innovative technological line for processing industrial doors made of wood materials. The achieved savings improve the competitiveness of the door manufacturer on the market. In order to calculate the material savings obtained in the production of the most important models of door leaves that can be obtained in machining on the TechnoPORTA line, numerical data were compiled specifying the dimensions of semi-finished products, taking into account machining allowances applied before and after reduction. The implementation of the TechnoPORTA line makes it possible to reduce the negative impact on the environment by reducing the consumption of wood. It reduces the consumption of materials and the operating costs associated with the reduction of labor intensity, the load on machines and devices, and inventory levels.